Penerapan Model Pembelajaran Flipped Classroom Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa Pada Materi Kesetimbangan - Febrian Solikhin; Hanif Nur Fadhil (Jurnal Ilmiah Kanderang Tingang, 2024)
This research is classroom action research (CAR) with the aim of improving students’ activities and learning outcomes in chemical equilibrium material by implementing the flipped classroom learning model. This research was conducted at SMAN 7 Bengkulu City with the research subjects being 38 students of class XI MIPA 4. The stages carried out were using the stages developed by Kemmis and McTaggart which included planning, action, observation and reflection in one cycle. This PTK is implemented in 2 cycles with each cycle consisting of 2 meetings. The instruments used were student learning activity observation sheets and test instruments. The results obtained were that student learning activity increased from 69.1% in cycle I to 87.02% in cycle II. Meanwhile, learning outcomes also increased from 61% in cycle I to 94% in cycle II.